Flood Risk Assessment and Forecasting for the Ganges-Brahmaputra-Meghna River Basins - Priya, Satya; Young, William; Hopson, Thomas; Avasthi, Ankit (World Bank, Washington, DC, 2017)
The Ganges Basin in South Asia is home to some of the world's poorest and most vulnerable communities. Impacted by catastrophic annual floods, the region is recognized as highly disaster prone, causing widespread human suffering and economic losses. In recognition of these challenges, many groups are actively and cooperatively engaged in reducing South Asia's vulnerability to flooding. As a contribution to these efforts, the World Bank recently commissioned specialist teams to assess and map flood risk across the Ganges River basin and to design and evaluate flood forecasting tools for the greater Ganges-Brahmaputra-Meghna basin. Flood Risk Assessment and Forecasting for the Ganges-Brahmaputra-Meghna River Basins summarizes the technical findings, includes highlights of the work, and links to the full technical reports and new interactive online resources. The report provides, for the first time, a numbers-based view of the impacts of floods of different severities across the Ganges basin, helping identify priority areas for addressing flood risks (for example, relocating levees, improving flood warning systems, and boosting overall economic resilience). This report on the flood forecasting system provides probability-based flood forecasts for more than 85 Ganges-Brahmaputra-Meghna basin locations along with near-real-time data maps of rainfall (predicted and actual) and river levels.